Financialisation embroils developing countries - Lapavitsas, Costas (Papeles de Europa, 2009)
Financialisation of developed countries includes increased lending to individuals as well as adoption of investment banking by commercial banks, thus contributing directly to the crisis of 2007-9. Financialisation has acquired an international aspect since the 1990s, primarily through liberalised capital flows. In the 2000s international financialisation has resulted in net capital flows from developing to developed countries, thus imposing substantial costs on the former, while subsidising the USA as leading issuer of quasiworld- money. International financialisation has also spurred domestic financialisation in developing countries through development of bond markets and foreign bank entry. Developing countries have been drawn into the crisis as current accounts declined and short-term capital flows were reversed.